Corals, Canyons, and Conservation: Science Based Fisheries Management Decisions in the Eastern Bering Sea - MacLean, Steve A.; Rooper, Christopher N.; Sigler, Michael F. (Frontiers in Marine Science, 2017)
When making science matter for conservation, marine conservation practitioners and managers must be prepared to make the appropriate decision based on the results of the best available science used to inform it. For nearly a decade, many stakeholders encouraged the North Pacific Fishery Management Council to enact protections for deep-sea corals in several canyons in the Eastern Bering Sea slope. In 2014, at the request of the Council, the National Marine Fisheries Service, Alaska Fisheries Science Center conducted a strip-transect survey along the Eastern Bering Sea slope to validate the results of a model predicting the occurrence of deep-sea coral habitat. More than 250,000 photos were analyzed to estimate coral, sponge, and sea whip abundance, distribution, height and vulnerability to anthropogenic damage. The results of the survey confirmed that coral habitat and occurrence was concentrated around Pribilof Canyon and the adjacent slope. The results also confirmed that the densities of corals in the Eastern Bering Sea were low, even where they occurred. After reviewing the best available scientific information, the Council concluded that there is no scientific evidence to suggest that deep-sea corals in the Eastern Bering Sea slope or canyons are at risk from commercial fisheries under the current management structure, and that special protections for deep-sea corals were not warranted.